Religiosity and female labour market attainment in Canada: the Protestant exception. Issue 3 (7th March 2016) - Dilmaghani, Maryam; Dean, Jason
Abstract : Purpose: – The relationship between religiosity and female labour market attainment has been widely investigated for the USA; however, no comparable study has been undertaken for the Canadian context. The purpose of this paper is to redress this critical oversight of the literature by examining the impact of religiosity on Canadian female labour supply, both at extensive and intensive margins. Design/methodology/approach: – Using data from the Canadian Ethnic Diversity Survey, the authors consider all the measurable dimensions of religiosity, for the pooled sample, as well as by religious group. A wide array of control variables is included in the regressions to insure the reliability of the estimates. Findings: – The authors find that overall religiosity inversely relates to female labour supply in Canada. When the impact of religiosity is assessed on a by religion basis, it is revealed that Protestant females are penalized, by far the most. Practical implications: – The result is comparable with the pattern uncovered in the USA for Conservative Protestant females. Unlike what can be expected, no statistically significant difference is detected between religious-nones and Catholics, suggesting a convergence of gender ideologies. Originality/value: – The investigation reveals interesting patterns that not only contribute to the current state of literature, but also motivate future research. Fairlie and Oaxaca-Blinder decomposition techniques are also used to further explore attainment gaps among the religious groups.